2018
DOI: 10.1016/j.joco.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Premium intraocular lenses: The past, present and future

Abstract: PurposeTo present potential benefits as well as limitations of premium intraocular lens (IOL) use, and provide insight in future of premium cataract surgery.MethodsBibliographic research was performed in PubMed/Medline database, and the most recently updated papers were evaluated. Keywords used were: premium intraocular lens, multifocal intraocular lens, toric intraocular lens, toric multifocal intraocular lens, accommodative intraocular lens, and the respective brand names.ResultsMultifocal IOLs provide uncor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
87
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 86 publications
(182 reference statements)
0
87
0
3
Order By: Relevance
“…Since Harold Ridley implanted the first intraocular lens (IOL) made of poly-methyl-methacrylate (PMMA) in 1949 [1] there have been significant improvements in surgical techniques, material developments [2], accuracy of preoperative measurements [3], and intraocular lens technology [4] in order to achieve complete spectacle independence after cataract surgery. Nowadays, different IOL designs are available in the market [5] such as toric IOLs to correct pre-existing corneal astigmatism, multifocal and accommodative to simultaneously provide good distance and near vision and aspheric IOLs to provide a better optical quality than the traditional IOLs with spherical optical design [6,7]. Aspheric designs are not limited to monofocal lenses; multifocal IOLs, toric IOLs or toric-multifocal IOLs and accommodative configurations may also include an aspheric surface [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since Harold Ridley implanted the first intraocular lens (IOL) made of poly-methyl-methacrylate (PMMA) in 1949 [1] there have been significant improvements in surgical techniques, material developments [2], accuracy of preoperative measurements [3], and intraocular lens technology [4] in order to achieve complete spectacle independence after cataract surgery. Nowadays, different IOL designs are available in the market [5] such as toric IOLs to correct pre-existing corneal astigmatism, multifocal and accommodative to simultaneously provide good distance and near vision and aspheric IOLs to provide a better optical quality than the traditional IOLs with spherical optical design [6,7]. Aspheric designs are not limited to monofocal lenses; multifocal IOLs, toric IOLs or toric-multifocal IOLs and accommodative configurations may also include an aspheric surface [8].…”
Section: Introductionmentioning
confidence: 99%
“…Presbyopia-correcting IOLs can be largely categorized depending on the optical principle and the number of foci generated [1][2][3]. Most IOLs use a diffractive-refractive optic, while others utilize different optical designs to provide multifocality [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that residents can achieve excellent visual outcomes after ATIOL surgery similar to those reported by experienced surgeons. [13][14][15] The majority of patients achieved good UDVA, UIVA and UNVA (88%, 93%, and 71%, respectively) at the POM3+ timepoint. Our UDVA results with ATIOLs are comparable to the UDVA results of resident-performed standard cataract surgery reported in several studies.…”
Section: Discussionmentioning
confidence: 94%
“…[6][7][8] Among the studied ATIOLs, AIOLs had good UIVA but did not perform as well for UDVA and UNVA at POM3+, which is similar to experienced surgeons' results in the literature. 15 This may also explain residents' lower preferences for this model. In both the wet-lab and operating room, we observed that AIOLs require additional surgical dexterity compared to the other ATIOL models, especially with the insertion maneuver.…”
Section: Discussionmentioning
confidence: 95%